A simplified modelling approach for thermal behaviour analysis in hybrid plasma arc-laser additive manufacturing - Wang, Chong; Sun, Yongle; Chen, Guangyu; Chen, Xin; Ding, Jialuo; Suder, Wojciech; Diao, Chenglei; Williams, Stewart (Elsevier, 2022)
Hybrid plasma transferred arc (PTA)-laser additive manufacturing (AM) has the potential to build large-scale metal components with high deposition rate and near-net shape. However, the process is complex with many parameters adjustable for process control, which determine the thermal behaviour and thus the final structure and properties of the deposited components. In this study, a three-dimensional steady-state finite element model with two independent circular surface heat sources was developed, validated, and used to analyse the thermal behaviour in hybrid PTA-laser AM of Ti-6Al-4V. Artificial conductivity in three orthogonal directions was applied in the melt pool to compensate for the melt pool convection effect. The predicted melt pool geometry, heat-affected zone and thermal cycles had good agreement with the corresponding experimental data. This model has advantages over the widely used volumetric heat source model, since it is more representative of the energy sources used, giving accurate thermal prediction for a wide range of process parameters. As the heat source parameters in this model are directly linked to the actual arc/laser size, it enables to capture heat source size effect on the hybrid process. In addition, it is easier to calibrate compared to the model with volumetric heat sources due to the fewer empirical parameters involved. It was found that in the investigated ranges of all the parameters, the melt pool geometry is more sensitive to laser power and travel speed compared to arc-laser separation distance and laser beam size. The full-field distributions of the cooling rate and temperature gradient in the hybrid process were obtained and the roles that different process parameters played on them were also studied, which provided useful thermal information for metallurgical analysis.
Keywords: Hybrid plasma arc-laser additive manufacturing; Steady-state finite element model; Orthotropic artificial conductivity; Melt pool geometry; Thermal variables